Upaya Guru Meningkatkan Sikap Sosial Siswa melalui Metode Diskusi pada Mata Pelajaran IPS - Binti Septiani; Muhammad Widda Djuhan (JIIPSI: Jurnal Ilmiah Ilmu Pengetahuan Sosial Indonesia, 2021)
In the teaching and learning process in schools it cannot be separated from the interaction process social, which is the main condition for the occurrence of social activities in the school environment. Activities teaching and learning related to social interaction, one of which is discussion. Attitude social is an act of someone to live in society like each other interact, help each other, respect each other, and so on. Social attitude is necessary developed because it can create a peaceful, harmonious, comfortable, and peaceful life atmosphere. When discussing Social Sciences lessons, the discussion method supports the course of social interaction by showing the social attitudes of each student. It was found at SMP Negeri 1 Balong according to the results of observations and interviews researcher, students of class VIII F in learning conditions, it appears that the students' social attitudes categorized as less good. As researchers found that students do not reflect honest attitude, courtesy, and lack of cooperation. As a first example, deviation of honest attitude is indicated when the teacher gives test questions or assignments then done individually, the result is that some children have cognitive abilities the less good and vice versa. The tendency of children with low cognitive performance actions that are less honest because they tend to rely more on students smart.